Analisis Sektor - Sektor Ekonomi Unggulan dan Strategi Pengembangannya: (Study Kasus di Kabupaten Lumajang) - Elok Rahmawati; Rafael Purtomo S; Duwi Yunitasari (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The growth rate of GRDP in Lumajang Regency tends to decrease significantly in the last 10 years. Even in 2019, the GRDP growth rate of Lumajang Regency was in the bottom 2 (two) after Probolinggo Regency in the Horseshoe Region and the bottom 3 (three) in East Java Province. From these data, it shows that Lumajang Regency needs an accelerated economic growth plan that focuses on leading economic sectors to improve the welfare of the people of Lumajang Regency. This study uses Shift Share and SWOT analysis. The results of the analysis of sectors that are recommended in accelerating economic growth are the Agricultural Sector, the manufacturing sector and the wholesale and retail trade sector, where the results of the SWOT analysis use the Growth oriented strategy or the Srength - Opportunity (S-O) strategy. The recommended strategy for developing the economic sector in the context of accelerating economic growth in Lumajang Regency is optimizing the improvement of the leading economic sector by utilizing technological advances, improving the quality of human resources, increasing the tourism sector and maximizing promotion. In addition, it is also necessary to pay attention to the synergy and linkages between sectors from upstream to downstream so that economic growth in all sectors will be achieved faster.